The Actions of Food Sellers about the Use of Styrofoam Containers - Silvy Silvy; Pipid Ari; Karina Nur Ramadhanintyas (Sarana Ilmu Indonesia (salnesia), 2022)
It is often found that they use styrofoam and plastic containers by people without the use of banana leaf mats or rice paper, so they do not understand the impact of using styrofoam on the environment and health. As an alternative to styrofoam and plastic food containers, you should use bamboo containers that are environmentally friendly. The purpose of this study was to analyze the relationship between the actions of food sellers regarding the use of styrofoam containers in the Gulun Field Madiun. The research design was quantitative using an analytical survey with a cross-sectional approach. The population was 80 people and asample of 67 subjects. This research was conducted in May 2022. The results showed that there was a significant relationship between independent variables, namely The results of the study found that there was a significant relationship between knowledge (p-value = 0,047) and attitude (p-value = 0,042) towards the action of using styrofoam containers in food vendors in Gulun Field, Madiun City. The conclusion of this study was that there was a significant relationship between the actions of using styrofoam containers in food vendors in the Gulun field in Madiun City. Researchers suggest traders to further enhance good actions by replacing the use of styrofoam containers with environmentally friendly containers and not endangering health.